Short-time fourier transform based transient analysis of VSC interfaced point-to-point DC system - Satpathi, Kuntal (2019)
The transient response of the voltage source converter (VSC) interfaced dc system is significantly different from the ac counterpart. The rapid discharge current from the dc-link capacitors and the vulnerability of the freewheeling diodes during the short circuit in dc grid demand that the transient detection algorithm executes within a few milliseconds. The rapidly rising fault current in the dc grid is expected to have high-frequency components which might be an effective indicator of the transient condition. This paper presents quantitative investigation of the high-frequency components utilizing short-time Fourier transform (STFT) during transient conditions. Detailed operating principles with various factors affecting the STFT operation such as ripple content of the input dc signal and window type and length have been thoroughly investigated. STFT algorithm is able to detect low-impedance faults within 1 ms and high-impedance faults in 2 ms. Moreover, it is able to distinguish between short-circuit fault and less severe transient conditions such as sudden load change. The STFT algorithm is evaluated analytically and subsequently applied to a MATLAB/Simulink based dc test system. It is further validated and substantiated with the real fault current data obtained from a scaled-down experimental testbed. Sensitivity analysis and comparison with the existing frequency-domain-based fault-detection method are done to support the efficacy of the proposed method.